Hypopituitarism after Gamma Knife radiosurgery for pituitary adenomas: a multicenter, international study - Cordeiro, Diogo; Xu, Zhiyuan; Mehta, Gautam U; Ding, Dale; Vance, Mary Lee; Kano, Hideyuki; Sisterson, Nathaniel; Yang, Huai-Che; Kondziolka, Douglas; Lunsford, L Dade; Mathieu, David; Barnett, Gene H; et al. (Journal of neurosurgery, 2019)
OBJECTIVE: Recurrent or residual adenomas are frequently treated with Gamma Knife radiosurgery (GKRS). The most common complication after GKRS for pituitary adenomas is hypopituitarism. In the current study, the authors detail the timing and types of hypopituitarism in a multicenter, international cohort of pituitary adenoma patients treated with GKRS. METHODS: Seventeen institutions pooled clinical data obtained from pituitary adenoma patients who were treated with GKRS from 1988 to 2016. Patients who had undergone prior radiotherapy were excluded. A total of 1023 patients met the study inclusion criteria. The treated lesions included 410 nonfunctioning pituitary adenomas (NFPAs), 262 cases of Cushing's disease (CD), and 251 cases of acromegaly. The median follow-up was 51 months (range 6-246 months). Statistical analysis was performed using a Cox proportional hazards model to evaluate factors associated with the development of new-onset hypopituitarism. RESULTS: At last follow-up, 248 patients had developed new pituitary hormone deficiency (86 with NFPA, 66 with CD, and 96 with acromegaly). Among these patients, 150 (60.5%) had single and 98 (39.5%) had multiple hormone deficiencies. New hormonal changes included 82 cortisol (21.6%), 135 thyrotropin (35.6%), 92 gonadotropin (24.3%), 59 growth hormone (15.6%), and 11 vasopressin (2.9%) deficiencies. The actuarial 1-year, 3-year, 5-year, 7-year, and 10-year rates of hypopituitarism were 7.8%, 16.2%, 22.4%, 27.5%, and 31.3%, respectively. The median time to hypopituitarism onset was 39 months.In univariate analyses, an increased rate of new-onset hypopituitarism was significantly associated with a lower isodose line (p = 0.006, HR = 8.695), whole sellar targeting (p = 0.033, HR = 1.452), and treatment of a functional pituitary adenoma as compared with an NFPA (p = 0.008, HR = 1.510). In multivariate analyses, only a lower isodose line was found to be an independent predictor of new-onset hypopituitarism (p = 0.001, HR = 1.38). CONCLUSIONS: Hypopituitarism remains the most common unintended effect of GKRS for a pituitary adenoma. Treating the target volume at an isodose line of 50% or greater and avoiding whole-sellar radiosurgery, unless necessary, will likely mitigate the risk of post-GKRS hypopituitarism. Follow-up of these patients is required to detect and treat latent endocrinopathies.
Keywords: acromegaly; pituitary adenoma; stereotactic radiosurgery; hypopituitarism; Cushing’s disease